1983
DOI: 10.1104/pp.72.3.685
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Salt Tolerance in a NaCl-Selected Stable Cell Line of Citrus sinensis

Abstract: A NaCi-tolerant cell lne which was selected from ovular callus of 'Shamouti' orange (Citrus sinensis L. Osbeck) proved to be a true cell lne variant. This conclusion is based on the following observations. (a) Cells which have been removed from the selection pressure for at least four passages retain the same NaCI tolerance as do cells which are kept constantly on 0.2 molar NaCI. (b) Na+ and Cl uptake are considerably lower in salt-tolerant cells (R-10) than in salt-sensitive cells (L-5) (2,3,25,28,30). Sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
53
0
5

Year Published

1985
1985
2003
2003

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(59 citation statements)
references
References 22 publications
1
53
0
5
Order By: Relevance
“…Whether or not this holds true for other cultivars or species remains to be verified. Recently, differential growth responses to salinity as affected by external calcium have been observed within a species (1,24). It would be interesting to know if these differences can be attributed to differences in displacement of membrane-associated Ca2`or to some other factor.…”
Section: Discussionmentioning
confidence: 99%
“…Whether or not this holds true for other cultivars or species remains to be verified. Recently, differential growth responses to salinity as affected by external calcium have been observed within a species (1,24). It would be interesting to know if these differences can be attributed to differences in displacement of membrane-associated Ca2`or to some other factor.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, while salt tolerant cells of tobacco accumulate Nae and Cl- (20,44), salt tolerant citrus cells accumulate less Nae and Cl-than do salt sensitive cells (1). Although most reports claim stability of the salt tolerance trait through prolonged periods of culture in the absence ofsalt (1,9,30,31,44), there are reports where tolerance was only stable in some lines (35) and we have reported a lack of stability of the salt tolerance phenotype of cells isolated in medium with 10 g L-`NaCl (18).…”
mentioning
confidence: 99%
“…Cell lines with enhanced tolerance to NaCl have been isolated from many glycophytic species (1,7,9,18,24,30,31,33,35,40,44) and various physiological processes appear to contribute to the adaptation of cells to salinity. For instance, while salt tolerant cells of tobacco accumulate Nae and Cl- (20,44), salt tolerant citrus cells accumulate less Nae and Cl-than do salt sensitive cells (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They further reported that embryoids regenerated from salt tolerant callus survived and grew better in saline media than embryoids regenerated from the original salt sensitive callus. Further, Ben-Hayyim and Kochba (1983) determined that the NaCl tolerant ovular callus line of Shamouti orange proved to be a true cell line variant. Matsumoto & Yamaguchi (1984) studied on the development of seven salt tolerant lines from EMS treated material and found that the lines with the highest salt tolerance were derived from the material which had undergone the highest exposure to EMS.…”
Section: Screening Of Citrus Rootstocks For Salt Toleance In Semi-arimentioning
confidence: 99%